A study of web privacy policies across industries. Issue 4 (2nd October 2017) - Nokhbeh Zaeem, Razieh; Barber, K. Suzanne
ABSTRACT: Today, more than ever, companies collect their customers' Personally Identifiable Information (PII) over the Internet. The alarming rate of PII misuse drives the need for improving companies' privacy practices. We thoroughly study privacy policies of 600 companies (10% of all listings on NYSE, Nasdaq, and AMEX stock markets) across industries and investigate 10 different privacy pertinent factors in them. The study reveals interesting trends: for example, more than 30% of the companies still lack privacy policies, and the rest tend to collect users' information but claim to use it only for the intended purpose. Furthermore, almost one out of every two companies provides the collected information to law enforcement without asking for a warrant or subpoena. We found that the majority of the companies do not collect children's PII, one out of every three companies lets users correct their PII but does not allow complete deletion, and the majority post new policies online and expect the user to check the privacy policy frequently. The findings of this study can help companies improve their privacy policies, enable lawmakers to create better regulations and evaluate their effectiveness, and finally educate users with respect to the current state of privacy practices in an industry.